Genetic characteristics of Plasmodium vivax from Northern Mali - Djimde, Moussa (Department of Integrative Biomedical Sciences (IBMS), 2019)
Introduction: The surprising presence of P. vivax in West Africa and their ability to infect a Duffy negative population is one more threat to public health. In order to contribute to malaria elimination efforts, there is a need to investigate the origin and characteristics of P. vivax population isolates in Northern Mali. Next Generation Sequence Analysis (NGSA) can help us understand parasite genetic characteristics although low parasite density is a challenge for whole genome sequencing (WGS). In the present work, we investigated if selective whole genome amplification (sWGA) can enrich P. vivax DNA extracted from Rapid Diagnostic Tests (RDTs) for Whole Genome Sequencing. We also investigated the origin and the susceptibility to antimalarial drugs of the strains isolated in Northern Mali. Methods: Parasite DNA was extracted from 267 RDTs using the QIAamp DNA mini kit, then nested PCR and 7 samples were positive for P. vivax. After sWGA, the whole genomes were sequenced using the Illumina platform. Next Generation Sequences Analysis was done followed by population differentiation analyses. Twenty-two additional P. vivax whole genomes from other parts of the World were downloaded from the European Nucleotide Archive for further Neighbour Joining analysis. Results: The sequences extracted from RDTs showed high contamination with human DNA (80%). From the parasite DNA, in total 69529 SNPs were found in the seven P. vivax strains of Northern Mali. The most significant p-values per SNP were carried by the chromosomes 2, 3, 4, 5, 12, 13 and 14. With regard to variant effects, the Transition/Transversion ratio was 1.1. The density of variants with a high effect was 1.62%. There was no mutation associated with antimalarial drugs resistance on pvcrt-o or pvmdr-1 genes. Pairwise differentiation suggests a high degree of relatedness between P. vivax strains isolated in Northern Mali. The NeighboursJoining analysis shows clearly that strains from Mali cluster together and are genetically distinct from those from Mauritania, which shares a border with Mali. The strains isolated in Northern Mali are genetically closer to those from Madagascar, India and Latina America. Conclusion: We did not identify mutations associated to the resistance to antimalarial drugs in pvcrt-o and pvmdr-1 genes. This study confirms that P. vivax strains genetically distinct from those of Mauritania are circulating in Mali. Finally, we conclude that sWGA is a feasible approach for P. vivax DNA enrichment for WGS despite the high proportion of human contamination.